Design of bedrooms and comfort rooms in Molave residence hall their functions and effects on the residents behavior - Nazareno, Marian Scarlet I.; Florendo, Raquel Baltazar (1989.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Molave Residence Hall, University of the Philippines Diliman; Bedrooms -- Designs and plans; Toilets -- Philippines; Dormitories -- Philippines